Microstructure and corrosion characteristics of cast silicon bronze in ammonia environment - Sekunowo, Olatunde; Durowaye, Stephen; Bello, Oluwatoyin (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Refrigerating systems operating on either the open re-circulation or chilled water circuits are proned to corrosion attacks. Often, the ensued corrosion products foul and inhibit efficient heat transfer within the system causing leaks resulting in catastrophic failures. Thus, the imperative to search for a material that can be an effective substitute for the conventional copper pipe used in most refrigerating systems. In this study, the microstructure and corrosion susceptibility of cast silicon bronze in anhydrous ammonia environment was investigated. The silicon bronze was produced by sand casting with the silicon varied from 1-4 wt. %. An accelerated electrochemical polarisation technique was employed to simulate the corrosion behavior of the cast alloy. The results show relatively low corrosion susceptibility, 0.75 mm/yr of the alloy in anhydrous ammonia. This may be attributed to the silicon dioxide (SiO2) passive film formed on the surface of the alloy. The effectiveness of the SiO2 passive film increases as the wt. % of silicon addition increased. The potential for drastic reduction in maintenance cost and frequency of call-backs of refrigerating units is enhanced by the outcome of this study.Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 1, 2017, Page: 56-65